Aloin protects against UVB-induced apoptosis by modulating integrated signaling pathways - He, Qi; Chen, Yu-Pei; Wu, Chun; Wu, Hongtan; Li, Fei; Li, Mingyu; Chen, Fangfang (Frontiers in Pharmacology, 2025)
Aloin, an anthraquinone compound, is naturally abundant in the Aloe. This study comprehensively investigates the photoprotective effects of aloin against UVB-induced damage in HaCaT cells, elucidating its antioxidant capacity and its role in preventing cellular apoptosis. Aloin demonstrated significant antioxidant activity in ABTS and DPPH assays, with a dose-dependent reduction in intracellular reactive oxygen species levels as evidenced by fluorescence analysis. Western blot analysis revealed that aloin inhibited the phosphorylation of both p38 and JNK, with a more pronounced effect on p38. This was further supported by IC50 values, indicating a higher inhibitory potency of aloin against p38 compared to JNK. Assessments using MTT, Hoechst, Calcein/PI staining, and flow cytometry collectively verified that aloin effectively mitigated UVB-induced apoptosis in cells. Proteomic analysis showed that aloin modulated the expression of proteins involved in critical signaling pathways, including PI3K-Akt, p53, TGF-β and pathways in cancer, promoting cell survival. Aloin upregulated proteins associated with cell cycle regulation and antioxidant responses, such as CCND3, GSTM4, GNA12, SKIL, YWHAZ, and PKN3 while downregulating pro-apoptotic protein FOXO3. These findings highlight aloin’s potential as a therapeutic agent for UVB-induced skin damage by effectively modulating cellular stress responses.